Space of Detention : The Making of a Transnational Gang Crisis between Los Angeles and San Salvador - Zilberg, Elana, 1963- (Book collections on Project MUSE., 2011)
An ethnographic analysis of the purported transnational gang crisis between the United States and El Salvador, based on extensive research in Los Angeles and San Salvador.